2019
DOI: 10.1021/acs.jpca.9b05065
|View full text |Cite
|
Sign up to set email alerts
|

Benzoxazine Formation Mechanism Evaluation by Direct Observation of Reaction Intermediates

Abstract: Benzoxazine formation is a fundamental step in the preparation of polybenzoxazine resins, and a detailed description of the mechanism governing the formation of benzoxazine and side products is vital for improving the properties and performance of these resins. Determination of the nature and properties of reaction intermediates is not trivial. Therefore, a Mannich-type condensation of aniline, formaldehyde, and phenol was evaluated as a potential method to form benzoxazine. Coupling positive mode electrospray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 73 publications
3
23
0
2
Order By: Relevance
“…This similarity is expected considering the shared anion and the closely related cationic structures. The values for m η / σ derived from the viscosity and conductivity data are shown in Table and, in ranging from 115–170, are of a similar order to values previously reported for fragile ILs . Furthermore, the values for the fragility indices derived from the two different quantities, viscosity ( m η ) and conductivity ( m σ ), show reasonable agreement between their magnitudes and respective trends.…”
Section: Resultssupporting
confidence: 81%
“…This similarity is expected considering the shared anion and the closely related cationic structures. The values for m η / σ derived from the viscosity and conductivity data are shown in Table and, in ranging from 115–170, are of a similar order to values previously reported for fragile ILs . Furthermore, the values for the fragility indices derived from the two different quantities, viscosity ( m η ) and conductivity ( m σ ), show reasonable agreement between their magnitudes and respective trends.…”
Section: Resultssupporting
confidence: 81%
“…For all mixtures, it is clear that the peak centered around 20 cm −1 at ambient pressure shifts toward higher wavenumbers as pressure increases, reaching ~45 cm −1 for p ~ 2 GPa. This broad band was previously related to intermolecular motions . The occurrence of saturation of the position and of the shape of the band above ~2 GPa suggests that molecular motions are hindered above this pressure, consistently with the formation of a glass state.…”
Section: Resultssupporting
confidence: 67%
“…Further support for the occurrence of a glass transition in MIX93‐7, MIX85‐15, and MIX50‐50 comes from the pressure dependence of their low‐wavenumber Raman spectra. For a better analysis, the detected intensity was transformed into Raman susceptibility defined as χ(ω) = I(ω)/(1 + n(ω)), where I(ω) is the Raman intensity and n (ω) = (e −βђω − 1) −1 is the thermal population factor . The susceptibility plot is reported in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The OPO As suggested in the literature, 14,51,52 bands calculated to be less It should be highlighted that previous studies showed that lowering the ion trap pressure to reduce collisional cooling and increasing the q-parameter to center the ion cloud in the laser beam path can further enhance the photofragementation efficiency when needed, 79,83,84 these compensating for low laser power or high dissociation thresholds.…”
Section: Opo/opa Optimizationmentioning
confidence: 83%
“…23,24 The main advantages of IRMPD spectroscopy over methods based on PID in other spectral regions [25][26][27][28][29][30][31] is that the IR spectral signatures allow the discrimination of functional groups, the analysis of conformational isomers and the identification of protonation/ coordination sites, especially when supported by theoretical calculations. 32,33 Consequently, IRMPD experiments have been used in an extensive number of systems and analytical applications, [34][35][36][37][38][39] from biomolecules, 40-42 drugs [43][44][45] and metabolites [46][47][48][49] to the evaluation of catalysis and reaction mechanisms, 19,[50][51][52][53][54][55][56] nanocalorimetry determinations 57,58 and in studies evaluating the electrospray ionization process 59 and aerosol composition. 60 Optical parametric oscillators (OPOs) coupled to optical parametric amplifiers (OPAs) deliver infrared radiation in the 2000-4500 cm −1 frequency range, allowing the evaluation of higher frequency modes such as O-H and N-H stretches.…”
Section: Introductionmentioning
confidence: 99%